The implementation of Literay at the Right Age Program in the Ceará State (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2019)
Abstract: Through its successful results, the Literacy Program in the adequate age (PAIC) placed Ceará in evidence in the Brazilian educational scenario, gaining prominence as the maximum expression of the collaborative system in the state. The aim of the PAIC is that all children are literate until the age of eight, and have in teacher training the essential component of teacher professionalization. Due to the complexity of attributions and competences in terms of coordination, which involves the transfer of financial resources and mechanisms of induction for adherence to these politics, this work aims to investigate how the discursive alignment occurs in its implementation. The research methodology uses narrative analysis to interpret the perception of the agents that interact in the implementation of the PAIC. The results show that the different hierarchical levels of the educational bureaucracy are reflected in the narratives and allow to establish a contrast between the agents' interaction forms and their respective perceptions and scope of action. Keywords: PAIC. Collaboration. Implementation. Narrative analysis. Literacy.